Fraud Diamond Model To Detecting Financial Reporting Fraud: Effectiveness Social Media Transparency as A Moderating - Juanda, Ahmad; Setyawan, Setu; Candra Inata, Lia (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: The purpose of this study is to test and analyze pressure factors, opportunities, rationalization and capability in detecting financial statement fraud. Also, testing and analyzing the effectiveness of social media transparency in moderating the perspective of the diamond fraud model to detect indications of financial statement fraud. Methodology/approach: The data used in this study are secondary data obtained by documentation techniques. The population of this study is all State-Owned Enterprise (SOE) companies in 2022. Findings: The results found that there was a positive influence between pressure, opportunity and the ability to detect financial statement fraud, while the negative effect was only found in rationalization. The effectiveness of social media transparency strengthens the relationship between pressure variables, rationalization, the ability to detect indications of financial statement fraud. Meanwhile, the effectiveness of social media transparency weakens the relationship between opportunity variables to detect indications of financial statement fraud. Practical implications: This research contribution can be used as input to companies to detect model factors, namely diamond fraud in detecting financial statement fraud and can be used for investors to be more careful in investing funding in certain companies through the impact of financial statement fraud. Originality/value: The Diamond fraud model in detecting financial statement fraud with its moderation variable is the effectiveness of social media transparency. This research is a replication and development of previous research, the difference: this study uses data from all state-owned companies, to strengthen the theory of the new diamond fraud model and ascertain whether it can be used as a reference to find out the causes of financial statement fraud, this study uses the effectiveness of social media transparency as a moderation variable